Державна політика України в інноваційній сфері: основа гарантування національної безпеки - Вовченко, О.В. (Наука та наукознавство, 2018)
Проаналізовано стан державної політики України в інноваційній сфері у порівнянні з провідними країнами світу та його вплив на забезпечення національної безпеки. Наведено дані про розвиток нанотехнологічної індустрії, які показують відставання України від провідних країн світу в цій сфері як за обсягами фінансування, так і за кількістю підприємств. Надано приклади українських компаній, які здобули передові позиції в нанотехнологічній індустрії. Зазначено, що для інституційного забезпечення інноваційної політики України пріоритетного значення набувають державні програми інноваційного розвитку промислового сектору. Наведено інформацію стосовно інструментарію забезпечення процесів стимулювання інноваційної діяльності, який застосовується у передових країнах світу. Проанализировано состояние государственной политики Украины в инновационной сфере в сравнении с ведущими странами мира и его влияние на обеспечение национальной безопасности. Приведены данные о развитии нанотехнологической индустрии, которые показывают отставание Украины от ведущих стран мира в этой сфере как по объемам финансирования, так и по количеству предприятий. Представлены примеры украинских компаний, которые вышли на передовые позиции в нанотехнологической индустрии. Подчеркнуто, что для институционального обеспечения инновационной политики Украины приоритетное значение приобретают государственные программы инновационного развития промышленного сектора. Приведена информация об инструментарии обеспечения процессов стимулирования инновационной деятельности, используемом в передовых странах мира. The quality of the innovation policy in Ukraine and its implications for the national security are analyzed. Data on the performance of nanoindustry are given, to show that Ukraine lags behind the advanced countries in this field by financing and by number of enterprises involved. Ukraine has no integrated legal document specifying key parameters, objectives and prospective directions of nanoindustry. Ukraine has no permanent official body charged with nanotechnology development, tax and customs stimuli have not been applied for business entities engaged in nanotechnology-related activities. The only preference for nanoindustry envisaged by the Customs Code of Ukraine is exemptions from custom duties for materials, raw materials and equipment used in nano-productions or operated by nanotechnologies. State orders for nanoproducts are not placed. At the same time, successful stories of Ukrainian companies that could win good positions in nanoindustry are given. It is emphasized that state programs for the innovation development of industrial sector have primary importance in the institutional support to the innovation policy in Ukraine. Information about tools for innovation promotion, used in advanced countries, is given.